Career-related teacher support as a secure base: an attachment theory model of career adaptability and future work self-salience among university students - Zhang, Yuan; Yu, Ying; Wang, Zhigang (Frontiers in Psychology, 2025)
IntroductionGlobal economic turmoil has intensified the youth employability crisis, with a 12.6% unemployment rate, leading to reduced future work self-salience (FWSS) among university students. Career education remains fragmented, often neglecting teachers’ dual role as attachment figures and providers of industry-relevant support. This study proposes that career-related teacher support (CRTS) enhances students’ career adaptability (CA) and FWSS based on attachment theory. Additionally, it examines how performance goal orientation (PGO) moderates these relationships.MethodsA nationally stratified random sample of 391 undergraduates from three university tiers in China completed questionnaires. Variables were assessed using validated Chinese scales. Mediation and moderation analyses were conducted using Hayes’ PROCESS macro in SPSS with 5,000 bootstrap resamples and 95% confidence intervals.ResultsSix of seven hypotheses (H1–H6) were supported. CRTS enhances FWSS and CA, with CA mediating the relationship between CRTS and FWSS. PGO exhibited a paradoxical dual role: it weakened the effect of CRTS on CA while strengthening the effect of CA on FWSS.DiscussionThis study demonstrates that CRTS functions as a secure base, enhancing CA and FWSS. CA accounted for 34.12% of the total effect of CRTS on FWSS. PGO’s paradoxical moderating effect suggests that while it weakens the link between CRTS and CA, it strengthens the path from CA to FWSS. These findings extend attachment theory into higher education, offering practical implications for integrating adaptability-focused modules into curricula and tailoring teacher support to counteract youth unemployment in uncertain labor markets.